Conference Digest. 2000 Conference on Lasers and Electro-Optics Europe (Cat. No.00TH8505)
DOI: 10.1109/cleoe.2000.909866
|View full text |Cite
|
Sign up to set email alerts
|

Multi-stripe tunable waveguide DFB laser for new type of laser spectroscopy

Abstract: The ah, the diabilihr, the stability and the mst of tunable lasers will be impmved v e q mvch by taking integrated waveguide structure. We have developed 80lid-8tate &+xibuted.feedback @FE9 dye laaera with I dye-doped PMMA waveguide The DPB laser action c m be attained by following two metho& 1) h d -t y p e DFB using photo-etched p t i n g dong the wavepuide, and 2) tvaableDPB urdng Wbeamintersetian ofpumpinghe..How-.e . planer vmvepuide is used in these experiments. Io this paper, we developed multi. shipe w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…7 By fabricating a DFB structure, a laser threshold of less than 1µJ and durability of more than 3 × 10 4 ∼ 6 × 10 4 shots were achieved. 8,9 We have also shown that these miniaturizing approaches can be used as a pico-second pulse generation system. 10,11 In this paper, we report about our recent studies on the all-plastic organic dye lasers as integratable tunable lasers.…”
Section: Introductionmentioning
confidence: 96%
“…7 By fabricating a DFB structure, a laser threshold of less than 1µJ and durability of more than 3 × 10 4 ∼ 6 × 10 4 shots were achieved. 8,9 We have also shown that these miniaturizing approaches can be used as a pico-second pulse generation system. 10,11 In this paper, we report about our recent studies on the all-plastic organic dye lasers as integratable tunable lasers.…”
Section: Introductionmentioning
confidence: 96%